Analysis the energy saving of Chiller Plant (CHIP) daily operation by using optimal projected capacity of Ice Thermal Energy Storage (ITES) - Shaari, SR; Othman, M. L.; H., Hizam; N. Y., Dahlan; Chik, Mohd Hanafiah; Yahaya, Mohamad Suhaimi; Abu Bakar, Hamzah; Zainal Anuar, Suhafizudin; Amir, Zulhelmi (IOP Publishing, 2021)
High total cooling load (COLA) relatively during peak and mid-peak as compared to off-peak hour's period requires more operating equipment of chiller plant (CHIP) to be operated during that period. The more operating equipment working, the more energy consumed is required to provide cooling thermal for COLA. High energy consumption of CHIP operation during peak and mid-peak hour lead high electricity cost due to higher energy charge charged by utility for every per kWh energy consumed by a CHIP operation. Therefore, this study aims to determine potential energy saving of CHIP operation by using optimal charging of ice thermal energy storage (ITES), then provide cooling thermal (COMA) for total COLA through discharging operation. Cooling thermal of ITES was charged based on maximum required COLA during peak and mid-peak hour. In this study, an optimization technique of linear programming was used to charge ITES optimally during off-peak hour. Analysis was conducted to compare the energy consumption of CHIP operation by using ITES discharging operation with the current practice of CHIP operator. This analysis showed that, the potential energy saving based on this strategy by using optimization technique is 27.89%.